Perbedaan Pengetahuan dan Perilaku Membaca Label Pangan Antara Mahasiswa Prodi Gizi dan Non Gizi Di Sekolah Tinggi Ilmu Kesehatan Baiturrahim Jambi - Afriza Riyanti; Dini Junita; Elvin Rosalina (Jurnal Akademika Baiturrahim Jambi, 2020)
The behavior of reading food labels is one of the Balanced Nutrition Messages. How to find out the safety of packaged food to be purchased by looking at food labels, but awareness of the importance of reading labels is still low. Nutrition students at STIKes Baiturrahim obtained courses related to food labeling and to make conclusions about the extent to which nutrition students understand and practice food labels, then a comparison group was made of non-nutrition students. The aim of this study was to found the differences in knowledge and behavior in reading food labels between nutrition and non-nutrition students at STIKes Baiturrahim.This study used a cross sectional study design that was conducted at STIKes Baiturrahim Jambi in May 2019. The research respondents were final year students at STIKes Baiturrahim from a group of 70 nutrition and non-nutrition students with a purposive sampling technique. Data collection uses a questionnaire about knowledge about food labels and food label reading behavior. Data were then analyzed using the Mann Whitney test for food label knowledge and the Independent Sample t-test for reading food label behavior. The results showed that there were no differences in knowledge and behavior in reading food labels between nutrition and non-nutrition students with p-values of each variable 0,203 and 0,554. For further research, it can be continued with the same or different variables by taking a variable on one of the food label information that is on food packaging with a more in-depth research method (qualitative).